A high level of serum neopterin is associated with rapidly progressive interstitial lung disease and reduced survival in dermatomyositis. (18th December 2019) - Peng, Q-L; Zhang, Y-M; Liang, L; Liu, X; Ye, L-F; Yang, H-B; Zhang, L; Shu, X-M; Lu, X; Wang, G-C
Summary: Neopterin is primarily synthesized and released by activated macrophages/monocytes upon stimulation with interferon-γ and is considered as a marker for macrophage activation. This study aimed to analyze the serum levels of neopterin in patients with dermatomyositis (DM) in association with clinical manifestations, laboratory data and patient prognosis. One hundred and eighty-two consecutive DM patients and 30 healthy controls were retrospectively enrolled into the study. Serum levels of neopterin were significantly increased in DM patients compared to healthy controls ( P < 0·001). High serum neopterin levels were associated with anti-melanoma differentiation-associated gene (MDA5) antibody, rapidly progressive interstitial lung disease (RP-ILD) and characteristic DM cutaneous involvement. Longitudinal assessment of serum samples revealed that the serum neopterin levels were closely correlated with disease severity (β = 30·24, P < 0·001). In addition, a significant increase in serum neopterin concentration of non-survivors was observed when compared to that of survivors ( P < 0·001). Receiver operator characteristic curves showed that serum neopterin could distinguish non-survivors and survivors at an optimal cut-off level of 22·1 nmol/l with a sensitivity and specificity of 0·804 and 0·625, respectively ( P < 0·001). Kaplan–Meier survival curves revealed that DM patients with serum neopterin > 22·1 nmol/l had a significantly higher mortality compared to the patient group with serum neopterin < 22·1 nmol/l (log-rank P < 0·001). Multivariate regression analysis identified high serum neopterin concentration to be an independent risk factor for poor prognosis in DM (adjusted hazard ratio = 4·619, 95% confidence interval = 2·092–10·195, P < 0·001). In conclusion, increased serum levels of neopterin were significantly associated with RP-ILD and reduced survival in DM patients, suggesting it as a promising biomarker in disease evaluation of DM. Graphical Abstract: